Human Performance Risks and Benefits of Adaptive Systems on the Flight Deck. Issue 1 (2nd April 2016) - Dorneich, Michael C.; Rogers, William; Whitlow, Stephen D.; DeMers, Robert
ABSTRACT: Objective : Human performance risks and benefits of adaptive systems were identified through a systematic analysis and pilot evaluation of adaptive system component types and characteristics. Background : As flight-deck automation is able to process ever more types of information in sophisticated ways to identify situations, it is becoming more realistic for adaptive systems to adapt behavior based on their own authority. Method : A framework was developed to describe the types and characteristics of adaptive system components and was used to perform a risk–benefit analysis to identify potential issues. Subsequently, eight representative adaptive system storyboards were developed for an evaluation with pilots to augment the analysis results and to explore more detailed issues and potential risk mitigations. Results : Analysis identified the principal drivers of adaptive "triggering conditions" risk as complexity and transparency. It also identified the drivers of adaptations risks and benefits as the task level and the level of control versus information adaptation. Conclusion : Pilots did not seem to distinguish between adaptive automation and normal automation if the rules were simple and obvious; however, their perception of risk increased when the level of complexity and opacity of triggering conditions reached a point where its behavior was perceived as nondeterministic.